2004
DOI: 10.1002/xrs.771
|View full text |Cite
|
Sign up to set email alerts
|

Trace element categorization of pollution sources in the equator town of Nanyuki, Kenya

Abstract: An air pollution campaign was carried out in the town of Nanyuki at four different sites during July and August 1999. Nanyuki is situated on the equator on the northwestern slope of Mount Kenya at about 1930 m above sea level. The intention of the project was to characterize aerosol elemental compositions in two size fractions, associated with specific natural and anthropogenic activities. A dichotomous impactor was used for sampling and an energy‐dispersive x‐ray fluorescence spectrometer was used for the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…[34] The concentrations were approximately 5-50 times higher for all elements at the two urban sites compared to the remote site on Mt Kenya. In Nanyuki [14] a similar fine/coarse ratio was obtained in the four sites of that study except for the S and Pb ratios which were more than twice the Nanyuki ratio in this study. In Nairobi [34] differences were noted for Ni, Rb and PM.…”
Section: Meteorology and Atmospheric Circulationsupporting
confidence: 86%
See 3 more Smart Citations
“…[34] The concentrations were approximately 5-50 times higher for all elements at the two urban sites compared to the remote site on Mt Kenya. In Nanyuki [14] a similar fine/coarse ratio was obtained in the four sites of that study except for the S and Pb ratios which were more than twice the Nanyuki ratio in this study. In Nairobi [34] differences were noted for Ni, Rb and PM.…”
Section: Meteorology and Atmospheric Circulationsupporting
confidence: 86%
“…[27 -29] CMB is a model that calculates the contributions of known sources to the aerosol that is measured at a receptor site using the known chemical constituent profiles and strengths of the source. Critical scrutiny of the observed elemental concentrations during the campaign together with knowledge from other measurements in Kenya [9,10,14] indicated that soil dust, biomass burning, vehicle emissions, sea salt and sulfate could be the dominant components that were likely to make major contributions to the aerosol mass at Mt Kenya. Organic compounds and some inorganic components like nitrates were also likely to significantly contribute to the aerosol, but our chemical analysis did not include these components and they were left out of the CMB.…”
Section: Receptor Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…These advantages make it a valuable tool for analysis of environmental samples like aerosol particles. [12] The EDXRF spectrometer used in this study is located at the department of physics, University of Lisbon, Lisbon, Portugal. This spectrometer uses a W x-ray tube as an excitation source, and a secondary target of Mo.…”
Section: Methodsmentioning
confidence: 99%